1993
DOI: 10.1002/j.1552-4604.1993.tb03910.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability Studies of Drugs with Nonlinear Pharmacokinetics: II. Absolute Bioavailability of Intravenous Phenytoin Prodrug at Therapeutic Phenytoin Serum Concentrations Determined by Double‐Stable Isotope Technique

Abstract: Measurement of the absolute bioavailability of phenytoin (PHT) derived from test doses of phenytoin prodrug (PPD) at therapeutic PHT serum concentrations is complicated by two problems: 1) the area under the serum concentration versus time curve (AUC) produced by a given size of test dose will vary directly with background PHT serum concentration due to the nonlinear pharmacokinetic properties of PHT; 2) PPD is more water soluble than PHT, making renal excretion of PPD more likely. The authors describe a doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…45 The conversion half-life was 9.3 2 2.7 minutes, which is substantially shorter than that reported in the subsequent 43 A similar half-life was estimated (8.0 * 2.9 min) in another study in which a single dose of intravenous fosphenytoin was admini~tered.~~ In six men with epilepsy receiving oral phenytoin, the estimated half-life was 8.80 2 7.24 minutes after a single dose of intravenous fosphenytoin administered as a stable isotope. 46 The AUC for phenytoin derived from this dose was bioequivalent to that of a n equimolar intravenous dose of a phenytoin sodium stable isotope. The conversion of fosphenytoin to phenytoin did not appear to be affected by preexisting concentrations of phenytoin.…”
Section: Metabolism and Eliminationmentioning
confidence: 87%
“…45 The conversion half-life was 9.3 2 2.7 minutes, which is substantially shorter than that reported in the subsequent 43 A similar half-life was estimated (8.0 * 2.9 min) in another study in which a single dose of intravenous fosphenytoin was admini~tered.~~ In six men with epilepsy receiving oral phenytoin, the estimated half-life was 8.80 2 7.24 minutes after a single dose of intravenous fosphenytoin administered as a stable isotope. 46 The AUC for phenytoin derived from this dose was bioequivalent to that of a n equimolar intravenous dose of a phenytoin sodium stable isotope. The conversion of fosphenytoin to phenytoin did not appear to be affected by preexisting concentrations of phenytoin.…”
Section: Metabolism and Eliminationmentioning
confidence: 87%
“…total/free/conjugated substance levels or blood/urine), consideration should be given to a self‐reference study of several doses of the reference product in order to determine which parameter/matrix may be optimal to assess bioequivalence. Use of surrogate parameters has not been successfully employed in bioequivalence studies of endogenous drugs to date. Nonlinearity is likely to be a frequent issue in bioequivalence studies of endogenous drugs given homeostatic mechanisms, saturable processes, interchangeable substance pools, etc. Therefore, in addition to the concepts described above, the dose most likely to distinguish potency differences should be considered in designing a biostudy to compare such drugs. Consideration should also be given to the dual stable isotope technique to demonstrate bioequivalence between test and reference formulations, a method that has been described for various ‘non‐endogenous’ drugs [25–30]. However, this method, which involves the substitution of chemical elements within the drug molecule by stable isotopes that are not subject to radioactive decay such as 2 H, 13 C or 15 N, is only feasible where isotopes can be incorporated into the chemical structure of both test and reference formulations during the manufacturing process.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in addition to the concepts described above, the dose most likely to distinguish potency differences should be considered in designing a biostudy to compare such drugs. 10 Consideration should also be given to the dual stable isotope technique to demonstrate bioequivalence between test and reference formulations,a method that has been described for various 'non-endogenous' drugs [25][26][27][28][29][30]. However, this method, which involves the substitution of chemical elements within the drug molecule by stable isotopes that are not subject to radioactive decay such as 2 H, 13 C or 15 N, is only feasible where isotopes can be incorporated into the chemical structure of both test and reference formulations during the manufacturing process.…”
Section: S Dissanayakementioning
confidence: 99%
“…The conversion half-life is 8–15 min; however, the exact site(s) of conversion has not been determined. The conversion occurs independent of prior phenytoin plasma concentration (Browne et al 1993). Also, no factors have been found that may affect conversion, including race, gender or age.…”
Section: Introductionmentioning
confidence: 99%